(untitled) (Eurasian Journal of Ecology, 2024)
The Koshkar-Ata tailings dump, with a volume of accumulated waste of more than 105 million tons today, poses a potential danger to the health of the population of nearby settlements when the wind blows toxic dust from the dried surface. Currently, due to the decline in production rates, a significant part of the dried pulp waste has been exposed, forming "dusty beaches". In order to minimize the negative impact of tailings dumps and improve the environmental situation, it is necessary to develop and implement highly efficient and cost-effective solutions. Solving the issues of stabilization of the water phase level and dusty "beaches" is a difficult task in terms of technical solutions, capital and operating costs. The article presents the results of experimental and computational studies to determine the evaporation rate in the Koshkar-Ata storehouse. According to the literature data, the average annual air temperature of the regions of the Mangyshlak region is +9.05 ° C. It was necessary to determine the average level of evaporation of water from the Koshkar-Ata tailing dump at an air temperature and a water temperature equal to +9 ° C. The results of the experiments established that there is a direct dependence of water evaporation on temperature, regardless of the content of mineral salts, and the average level of evaporation of water from the Koshkar-Ata tailings dump at air and water temperatures equal to + 9 ° C is 0.3 cm. According to calculations over the past fifteen years, the value of water losses for evaporation and filtration in the settling pond of the Koshkar-Ata tailings pond is 1,201 m/year. It can be tentatively assumed that the share of filtration waters accounts for about 9-10% of the total losses, then these losses in height will amount to 0.106 m, i.e. 8.8% of the total loss level. Key words: pond, evaporation, water inflow, temperatures, tailings, process modeling, dry air, water vapor, temperature, element.